Kuat Geser Tanah Pasir yang Distabilisasi Menggunakan Aspal Cair SC60-70 - Elfira Resti Mulya, Willis Diana , (Jurnal Semesta Teknika, 2012)
Soil is one of the most important parts in construction work. Soil being found in the field are vary in terms of its properties, and its quality usually does not meet the specified requirements for building construction on it including sandy soil. Sandy soil does not have cohesion value (c), so its shear strength is very low and can lead to collapse. Because of that, it needs to be stabilized to improve the parameter of soil shear strength which are friction angle value (Ï) and cohesion value (c). Stabilizing material being used in this research is asphalt, in order to improve cohesion and soil density. Asphalt being used in this research is emulsified asphalt SC 60-70 which is Asphalt Cement (AC) dissolved in diesel oil. In this research, the shear-strength ofÂ  sandy soil stabilized with emulsified asphalt SC 60-70 was analyzed by means of direct shear-strength testing. It can be concluded from the result that friction angle tends to increase with the increase of the asphalt content. It can also be shown that the lowest friction angle value was found being at 0% asphalt content, 35,753Â°, while the biggest friction angle value was found being at 5% asphalt content, Â 38,970Â° (increased 10,169%).